Rancang Panel Surya Untuk Instalasi Penerangan Rumah Sederhana Daya 900 Watt - Mahmud Idris (LPPM Politeknik Jambi, 2019)
The need for electrical energy for humans continues to increase as the number of people increases and the increasingly modern pattern of human life is also one of the causes of increasing energy consumption. The solution to this discussion is to supply new and renewable energy sources as an alternative to supply electricity with the PLTS electricity system with a spare battery. The purpose of this study is to make a PLTS electrical system with a backup battery with a capacity of 900 Watts for power consumption from the National Electric Company and the Utilization of the Sun's Natural Resources into electrical energy. The PLTS system is in a backup battery for storing electrical energy produced by solar cells. PLTS and pendungung components are needed to produce PLTS with 900 Watt power, PLTS backup battery with 200 Ah battery capacity with 12V voltage, 150Wp x 2 Photovoltaic, MPA type solar charge controller with 30A capacity, Pure sine wave type inverter with 1000 Watt capacity and use safety current MCB 1 phase 6A and 2A.